2017
DOI: 10.19044/esj.2016.v13n3p279
|View full text |Cite
|
Sign up to set email alerts
|

Déterminants Et Contraintes De La Pratique De L’apiculture Dans Les Communes De Djidja Et Zogbodomey Au Sud Du Bénin (Afrique De l’Ouest)

Abstract: Beekeeping is a very interesting activity having a positive impact on agricultural production and rural incomes. This study conducted in both municipalities of Djidja and Zogbodomey, in southern Benin, aimed at analyzing the determinants and constraints of beekeeping activities. For this purpose, a sample of 110 beekeepers randomly selected was investigated. Data about socio-economic and demographic characteristics of households as well as the difficulties in beekeeping were collected through individual interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…Most plants in the Savannah area of the country blossom, in November corresponding to the end of the rain season which also coincides with stronger bee populations [ 12 , 14 , 31 ]. Our findings supported as found by Paraiso et a l. [ 27 ] that, November to January, when most beekeepers harvest their hives, and many feral colonies are destroyed by honey hunters in the entire country may be considered as the honey flow season in the northern parts of Benin. The positive correlation between the collected pollen and the pollen species frequency supported the increased collection of pollen and nectar from the same plant species or groups of plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most plants in the Savannah area of the country blossom, in November corresponding to the end of the rain season which also coincides with stronger bee populations [ 12 , 14 , 31 ]. Our findings supported as found by Paraiso et a l. [ 27 ] that, November to January, when most beekeepers harvest their hives, and many feral colonies are destroyed by honey hunters in the entire country may be considered as the honey flow season in the northern parts of Benin. The positive correlation between the collected pollen and the pollen species frequency supported the increased collection of pollen and nectar from the same plant species or groups of plants.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the beekeeping potentials, traditional beekeeping is common with Kenyan top bar and endogenous hives in jars, tanks, and tree barks [ 27 ]. Parasitic pressure is exceptionally low in the region where it is limited to varroas, the widespread small hive beetle ( Aethina tumida), and predators which may impact apiaries.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that women were poorly represented (6.25% in beekeeping organizations). These observations of poor women's involvement in beekeeping are similar to those obtained by Diouf (2002) in Senegal, Tchoumboue et al (2001) in the highlands of West Cameroon and in North-East Benin by Ahouandjinou (2016) and Paraïso (2017). Those studies showed that beekeeping was essentially practiced by men around Africa.…”
Section: Discussionsupporting
confidence: 88%
“…Our results confirm Diouf's (2002) who showed that 85% of beekeepers interviewed had farming as their main activity. They are also similar to those obtained in Benin by Yédomonhan (2009) and Paraïso (2017) where beekeepers had farming as main activity. In highlands of West Cameroon, Tchoumboue et al (2001) found that most farmers were state workers (16.3%) and students (5.4%) This was also observed in Togo with 58.92% of farmers (Sokemawu, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation